Pengembangan Media Detektor Warna Berbasis IoT Untuk Mengenalkan Warna Pada Siswa Autis Kelas I Di SLB-C YPPLB Makassar - Khaerani Awinar; Bastiana Bastiana; Siti Kasmawati (-, 2025)
Students with Autism Spectrum Disorder (ASD) have unique characteristics, including difficulties in understanding visual stimuli such as colors. On the other hand, the learning process in Special Needs Schools (SLB) still tends to be conventional and lacks the use of media that meets the sensory needs of autistic children. The lack of interactive, contextual, and technology-based learning media is one of the inhibiting factors in introducing color concepts. Therefore, this study aims to develop an Internet of Things (IoT)-based color detector as a learning aid to introduce colors to autistic students. This research aims to develop an IoT-based color detector as a color recognition tool for autistic students at SLB-C YPPLB Makassar. The research method used is Research and Development (R&D) with the 4-D development model (Define, Design, Develop, Disseminate), although this study is limited to the Development stage. The results show that the IoT-based color detector media is highly needed by both teachers and students in the color learning process. The media development process involved several stages, including needs analysis, design planning, and validation by content and media experts. The media was designed by integrating a color sensor and speaker with an IoT system to provide an interactive and engaging learning experience for students. The results of the content and media expert validations indicate that the media is fairly valid and usable, though minor revisions are required, implying the overall quality of the media is fairly good. Furthermore, responses from teachers also indicate that the media is practical and effective in helping autistic students recognize colors.